A COMUNICAÇÃO ORGANIZACIONAL: UM ESTUDO EPISTEMOLÓGICO - Fonseca Júnior, Wilson Corrêa da (2007)
This work consists of an epistemological study having for object the production theory and methods of Organizational Communication in Brazil and above. The thesis searched to identify, to describe, to compare and to evaluate the main denominations, theoretical schools, philosophical entailing and conditioning social factors. For the enterprise it was necessary the elaboration of an ample bibliographical revision in epistemology, as well as a proposition of a specific methodology for epistemological studies. This methodology contemplates qualitative propositions, proceeding from Philosophy and quantitative propositions, proceeding from Information Science (Bibliometry and Scientometry), among others. Were analyzed 1,181 records and 517 documents available from the international database Web of Science and literature produced in Brazil and above on the subject. The study demonstrated that, in its hegemonic conception, Organizational Communication is marked deeply by management sciences and conceived as a set of practices and activities of communication for corporation effectiveness. However, while social and historical reality, Organizational Communication is a much more ample and extensive subject, due not only to the existence of diverse organization forms, but also because organizations interactions, in the current net society configuration, is each time more complex.(AU)